Artistic and aesthetic education of senior pupils by means of modern popular music - Могілей, Ірина (Pedagogy of Higher and Secondary Education, 2014)
Mogiley I. V. Artistic and aesthetic education of senior pupils by means of modern popular music. The article discusses the current trends of teaching art culture in high school. Based onthe analysisandsynthesis of scientific information specified entity definitions «aesthetic education»,«art education», «modern popular music» in terms of art formation. Proposed forms and methods of art-aesthetic education with contemporary popular music.